Comparative Effect of Lisinopril and Fosinopril in Mitigating Learning and Memory Deficit in Scopolamine-Induced Amnesic Rats - Debasree Deb; K. L. Bairy; Veena Nayak; Mohandas Rao (Hindawi Limited, 2015)
Lisinopril and fosinopril were compared on scopolamine-induced learning and memory deficits in rats. A total of eighty-four male Wistar rats were divided into seven groups. Group I received 2% gum acacia orally for 4 weeks, group II received normal saline, and group III received scopolamine (2 mg/kg/ip) as single dose. Groups IV and V received lisinopril ( 0.225 mg/kg and 0.45 mg/kg), while Groups VI and VII received fosinopril (0.90 mg/kg and 1.80 mg/kg), respectively, orally for four weeks, followed by scopolamine (2 mg/kg/ip) given 45 minutes prior to experimental procedure. Evaluation of learning and memory was assessed by using passive avoidance, Morris water maze, and elevated plus maze tests followed by analysis of hippocampal morphology and quantification of the number of surviving neurons. Scopolamine induced marked impairment of memory in behavioral tests which correlated with morphological changes in hippocampus. Pretreatment with fosinopril 1.80 mg/kg was found to significantly ameliorate the memory deficits and hippocampal degeneration induced by scopolamine. Fosinopril exhibits antiamnesic activity, indicating its possible role in preventing memory deficits seen in dementia though the precise mechanism underlying this effect needs to be further evaluated.